THE ROLE OF SURVEILLANCE TECHNOLOGY IN THE INVESTIGATION PROCESS OF CYBER CRIMES: A LEGAL PERSPECTIVE IN INDONESIA - Maryanti, Dwiningsih; Saputra Ardianto, Dwi; Mustika, Dian (Institut Teknologi Bisnis dan Kesehatan Bhakti Putra Bangsa Indonesia, 2024)
The development of digital technology has had a significant impact on various aspects of life, including in the field of law enforcement. In Indonesia, cybercrime is increasingly complex, demanding a more sophisticated and effective investigative approach. One of the approaches adopted is the use of surveillance technology in the investigation process. This article explores the role of surveillance technology in the investigation of cybercrimes, focusing on legal perspectives in Indonesia. Through juridical analysis, this article identifies the types of surveillance technologies used by law enforcement officials, such as surveillance software, online activity monitoring, and big data analysis. The article also examines the legal implications of using such technologies, including privacy concerns, the legality of electronic evidence, and the challenges of ensuring compliance with applicable laws and regulations. In the context of Indonesia, this article highlights the need for more specific and clear regulations to regulate the use of surveillance technology so as not to violate human rights, as well as the importance of training for investigators in operating such technology. Thus, this article provides an in-depth look at the dynamics of the use of surveillance technology in the investigation of cybercrime in Indonesia and its relevance in fair and effective law enforcement.